Estimulación oportuna: ventajas para el desarrollo de su hijo - Natalia Salas-Guzmán; María Ester Morales-Ramírez (Revista Electrónica Educare)
Early stimulation presents as it’s principle that “the earlier the child learns, better and more advantages he/she will obtain from the future” (Bravo and Pons, año 1, Nº5, p.66).